2008
DOI: 10.1002/chin.200850123
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis of Novel Pyrazolo[5,1‐b]benzothiazoles: A New Pericyclic Pathway.

Abstract: Benzothiazole derivatives R 0270Synthesis of Novel Pyrazolo[5,1-b]benzothiazoles: A New Pericyclic Pathway. -N-Amination of the benzylbenzothiazoles (I), followed by reaction of the N-amino salts (III) with ethyl orthoformate (IV) afford derivatives (V) of the pyrazolobenzothiazole ring system. The ring closure may proceed via deprotonation of the N-amino salt and subsequent electrocyclization to provide the tricyclic ring system. From a theoretical point of view, the pericyclic nature of the ring-closure step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…A set of previously synthesized benzothiazole and 3-amino-benzothiazolium derivatives [16] tested for DNA topoisomerase II inhibitory activity were chosen from our previous study [21] as shown in Table 1. The DNA topoisomerase II inhibitory activities of these compounds are represented as IC 50 values in the millimolar, micromolar or nanomolar range [21].…”
Section: Molecular Structures and Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…A set of previously synthesized benzothiazole and 3-amino-benzothiazolium derivatives [16] tested for DNA topoisomerase II inhibitory activity were chosen from our previous study [21] as shown in Table 1. The DNA topoisomerase II inhibitory activities of these compounds are represented as IC 50 values in the millimolar, micromolar or nanomolar range [21].…”
Section: Molecular Structures and Optimizationmentioning
confidence: 99%
“…Our group has been working for many years on the synthesis of some new heterocyclic compounds that were potentially DNA topoisomerase I and II inhibitors, and molecular modelling studies of these compounds [15][16][17][18][19][20][21]. So far some of the compounds exhibited significant topoisomerase II inhibitory activity with IC 50 values differing from 11.4 and 46.8 μM compared with the standard drug etoposide [15,18].…”
Section: Introductionmentioning
confidence: 99%